Factores socioculturales y su relación con la práctica de valores éticos y morales en los alumnos del nivel primario de la I.E.E José Carlos Mariátegui - Hernández Quispe, Edin Jeyler (2011)
Show it investigation this one once the existent relation among the factors was referred to determine socioculturales and he practices it of ethical moral values and morals in the primary level's pupils of the lnstitution Educativa Experimental. "José Carlos Mariátegui" of the sector Rupacucha, Rioja's district. The investigation's purpose is to determine positiva relation or existent refusal among the factors socioculturales and he practices it of ethical moral values and morals. Stop that way defining if alternating hypothesis is accepted her as he tells than the factors socioculturales to us they relate with significantly the moral values practica; 1 marry contrary serióus rejected and accepted the void hypothesis; All this wilt depend on the result that is obtained in the dataprocessing. In this sense 1 drink as person giving a reference to a sign once was constituted for 67 students of the lnstitution Educativa Experimental's primary level. "José Carlos Mariátegui" of the sector Rupacucha, Rioja's district. Correlaciona! is investigation of descriptiva fellow; the study population was shaped for the mentioned institution's 67 students. The shaped technician of the opinion poli for 40 items of questions balanced out applied herself In order to the information's anthology; As they are 7 of them to evaluate the respect, 7 to evaluate the responsibility, 6 to evaluate solidarity; 8 to evaluate the familiar relation, 5 to evaluate the environment student and 7 to evaluate means of communication (T.V.). The aftermaths were the following: The 25. In order to the information's processing, descriptiva statistics was utilizad, achieving the result of the intervening- hypothesis test the distribution's applícation t 2) freedom degrees with an acceptance zone of the 95. In this way study confirms alternating hypothesis and it rejects void hypothesis, demonstrating socioculturales relate with directly the ethical- moral values practica and the lnstitution Educativa Experimental's morals with it than the factors. "José Carlos ~ariátegui" of the sector Rupacucha, Rioja's district.